Application of The Mediated Learning Experience (MLE) Program in Improving Caregiver Interaction with Children 3-4 Years Old - Hermito Gidion; Frieda Maryam Mangunsong; Mita Aswanti Tjakrawiralaksana (Jurnal Ilmiah Psikologi MIND SET, 2021)
This study aims to determine the effectiveness of the mediated learning experience (MLE) training program in increasing caregiver interaction with children through brushing their teeth. The Mediated Learning Experience (MLE) program which focuses on learning experiences through mediation and active communication processes between caregivers and children to build interactions. This study used a quasi-experimental method one group pre-test and post-test design, with four participants. The criterion of participants are caregivers having children aged 3-4 years old, and lives in Jabodetabek. Measurements in this study used the non-parametric statistical test Wilcoxon Signed-Ranks Test. The pre-test results showed (M = 1.50; SD = 1.00) and post-test (M = 10.50; SD = 10.00) with a significant score, namely Z = -2,000, and the P-value (Asymp. Sig. 2-tailed) of 0.046, This score is less than critical research limit value of 0.05. It means that there is a significant increase in the caregiver’s interactions in brushing their teeth after being given the intervention using the Mediated Learning Experience (MLE) program.